The effect of endophyte (Neotyphodium uncinatum) in meadow fescue on grass grub larvae - Popay, A.J.; Townsend, R.J.; Fletcher, L.R. (New Zealand Plant Protection, 2003)
Grass grub (Costelytra zealandica) population density mean larval weight and visible damage were lower in meadow fescue (Festuca pratensis) infected with the endophyte Neotyphodium uncinatum (E) than in uninfected meadow fescue (E) in an unreplicated field trial In two bioassays third instar grass grubs ate all meadow fescue E roots but significantly less of the E roots Larvae fed E roots lost weight at the same rate as unfed control larvae Larvae given a choice between maize and either E or E meadow fescue in a pot trial consumed 33 more of the maize in the E treatment than in the E treatment Weight gain of larvae in E treatments was significantly less than in E in both the choice and nochoice pot trials but survival was the same It was concluded that meadow fescue infected with N uncinatum deters grass grub larval feeding but has no major toxic effects